(untitled) (Research, Society and Development, 2021)
Introduction: Teachers who were used to traditional teaching had the challenge of preparing classes and presenting them with the aid of tools never used by them, in addition to the orientation of reduced time. Some of these challenges are being resolved by institutions. Methodology: This is a reflective study, built on the basis of critical reading of scientific articles on remote learning during the COVID-19 pandemic. As it is a theme focused on education, we sought to base it directly on magazines and materials on the subject. Results and discussion: Technologies appear in the 2014-2024 National Education Plan as powerful transforming agents in education. However, it still needs advances and financial investments for its structuring in the educational sphere. In the pandemic, students began to experience a virtual environment, which demanded greater participation from them as protagonists in the teaching-learning process. Teachers say that education is impaired, that interaction between them and students is difficult, as well as keeping up with everyone, as they need more time to prepare classes for remote activities. Final Considerations: From the analysis of data on teaching in the COVID-19 pandemic, it is possible to see how much education has weakened in its structures at all levels of education. The lack of physical and technological resources has highlighted inequality, which for many was not yet noticeable.